Palm and Treo hacks - MacHaffie, Scott Andrew (O'Reilly, 2005)
Palm OS is one of the most popular handheld operating systems on the planet. From the newest Tungstens and Treos all the way down the family tree, Palms are everywhere. Although the Palm OS is simple to learn and use, there is more to it than meets the eye--from new features in the Palm to capabilities you can get with add-on software, the Palm can be made to do quite a lot. Palm and Treo Hacks gives you tips and tools that show you how to make the most of your Palm. A few minutes spent reading some of the hacks in this book will save you hours of research. Inside this book, you'll learn how to: Find great applications for your Palm and make the most of the ones you're using now Get super-organized, getting more from the built-in Personal Information Manager and learning how to manage complex projects with your Palm Extend the Palm with must-have software and hardware add-ons Take your Palm online, reading email, surfing the web, and sending instant messages Get some rest and relaxation with your Palm, whether it's listening to music, playing classic games, or watching video Written for beginning to experienced Palm users, Palm and Treo Hacks is full of practical, ingenious tips and tricks you can apply immediately. Whether you're looking to master the built-in applications or you want to trick out your Palm to its fullest extent, this book will show you how.